Integration of Islamic Sex Education Values into Islamic Religious Education: An Analysis from the Perspective of the Qur’an and Hadith - Dewi Masitoh; Ahmad Zumaro; Khoirotun Nisa (MASI Mandiri Edukasi, 2026)
The growing prevalence of adolescent sexual misconduct, including promiscuity, sexual harassment, and exposure to pornography, highlights the urgent role of Islamic Religious Education in fostering moral awareness and character formation among Muslim youth. This study aims to examine the Al-Qur'an and Hadith perspectives on sex education, analyze the core values of Islamic sex education, and explore how these values can be integrated into the teaching of Islamic Religious Education. This research uses a literature-based qualitative approach using thematic analysis of Al-Qur'an verses and Prophetic traditions related to sexuality, supported by relevant scientific literature in Islamic education and ethics. Findings show that the core values of Islamic sex education include personal purity (iffah), control of desires, moral responsibility, preservation of dignity, and ethical social behavior. These values can be systematically integrated into the teaching of Islamic religious education through the domains of aqidah, morals, fiqh, and date, especially through contextual learning strategies and teacher moral examples. This study concludes that sex education based on the Qur'an and Hadith not only serves as a framework for preventing moral deviations but also as a foundation for building strong character among Muslim youth.